2019
DOI: 10.1029/2019jd030684
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Blowing Snow Over the Tibetan Plateau With the Community Land Model: Method and Preliminary Evaluation

Abstract: Snow cover in mountainous terrain plays an important role in regional and global water and energy balances, climate change, and ecosystems. Blowing snow is a frequent and important weather phenomenon over the Tibetan Plateau (TP); however, this process is neglected in most current land surface models, despite the consequential role it plays in the land surface and atmospheric water and energy budgets. In this paper, we present a blowing snow model PIEKTUK coupled with the Community Land Model (CLM4.5) to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 70 publications
0
35
0
Order By: Relevance
“…2, but for the climatological average of ground temperature and first-layer (except for the observations at depths of 0 cm) soil temperature, soil moisture and soil heat flux. of the cold-region processes, particularly on the TP (Xia et al, 2014;Toure et al, 2016;Orsolini et al, 2019;Xie et al, 2019). Long-term, high-quality and high-temporalresolution observational data in the Third Pole region are not only extremely scarce, but are also very important for a deeper understanding of the key land surface processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, but for the climatological average of ground temperature and first-layer (except for the observations at depths of 0 cm) soil temperature, soil moisture and soil heat flux. of the cold-region processes, particularly on the TP (Xia et al, 2014;Toure et al, 2016;Orsolini et al, 2019;Xie et al, 2019). Long-term, high-quality and high-temporalresolution observational data in the Third Pole region are not only extremely scarce, but are also very important for a deeper understanding of the key land surface processes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it also acts as the "Water Tower of Asia" (Immerzeel et al, 2010). Numerous research indicates that the TP plays an essential role in controlling regional and global climate through its thermal and mechanical mechanisms (Manabe and Broccoli, 1990;Yanai et al, 1992;Duan and Wu, 2005;Liu et al, 2007). It exerts major control on atmospheric circulation at the local and continental scale (Ding, 1992;Ye and Wu, 1998;Li et al, 2018) through its latent heat release (Wu et al, 2016) and interactions between the Asian monsoon and midlatitude westerlies (Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The accurate classification of blowing snow events is important in numerical models which include blowing snow, as it determines whether or not invoke the parameterizations for sublimation and transport associated with blowing snow processes in the model (Lenaerts et al, 2012b;Xie et al, 2019). This paper described the construction and evaluation of the machine https://doi.org/10.5194/hess-2021-119 Preprint.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, internal physical properties of the snowpack, such as snow particle bonding, cohesion, and its kinetic properties, greatly influence the strength of snow resistance, which determines the initiation and persistence of blowing snow events (Li and Pomeroy, 1997b;Pomeroy and Gray, 1990;Schmidt, 1980). Previous studies have shown a sharp contrast in the threshold wind speed for snow transport between fresh snow and aged snow (Huang et al, 2008;Liston et al, 2007;Pomeroy 2005;Xie et al, 2019), owing to the strength of the bond between snow particles depending on destructive metamorphism, melting, snow loading, and increased compaction caused by overburden (Li and Pomeroy, 1997a, b;Oleson et al, 2010). Newly fallen snow particles are characteristically soft and powdery, with relatively low density, and are generally drier and less viscous than the deposited snow, making new snow particles much more likely to be lifted by the wind.…”
Section: Datamentioning
confidence: 99%
“…For instance, 19 LSMs in CMIP5 overestimate snow depth over the QTP (Wei and Dong, 2015), which could result in variations in the soil hydrothermal regime with respect to the aspects of magnitude and vector (cooling or warming) (Zhang, 2005). Moreover, most of the existing LSMs are not originally developed for permafrost regions: many of their soil processes are designed for shallow soil layers (Westermann et al, 2016), but permafrost occurs in the deep soil; moreover, the soil column is often considered to be homogeneous, which cannot represent the stratified soil that is common on the QTP (Yang et al, 2005). Given the numerous LSMs and their possible deficiencies, it is necessary to assess the parameterization schemes for permafrost modeling on the QTP, which is helpful for identifying the influential sub-processes, for enhancing our understanding of model behavior and for guiding the improvement of model physics (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%